Found-footage film - documentário de arquivo: o cinema de Emile de Antonio e uma análise de In The year of the pig - Altafini, Thiago (Universidade Federal de São Carlos, 2012)
A conceptual overview about documentaries made from archival footage, named foundfootage films. The main reference for the analysis of cinematographic production for the period prior to the year 1960 is the book Films Beget Films, published in 1964 by the American researcher Jay Leyda. This essay seeks to complement the research of Jay Leyda addressing aspects of the biography and work of American filmmaker Emile De Antonio, pointing out the relevance of your audiovisual production in the field of documentary from the use of archival material. The documentary In The Year of the Pig (1968) and his fragmentary, enigmatic and somewhat didatic historical narrative, are subjected to analysis. The goal of this study is an approximation of the De Antonio`s narrative with the concept of historical allegory in the film, according to Brazilian researcher Xavier, based on the ideas of Walter Benjamin on modernity and the role of allegory in the process of reinterpreting history and culture.
Keywords: Documentário (Cinema); Filme cinematográfico arquivos; Vietnã, Guerra do, 1961-1975; De Antonio, Emile, 1819-1989; História; Arquivo; Alegoria; Documentary; History; Found-footage; Allegory; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA